21st Century Mathematics Learning Challenges: Bibliometric Analysis of Trends and Best Practices in Shinta Indexed Scientific Publications - Safitri, Niken Dwi; Darmayanti, Rani; Usmiyatun, Usmiyatun; Nurmalitasari, Dewi (Universitas PGRI Madiun, 2023)
This study aims to find out the issues or problems that become the direction and trends of mathematics education research as an effort made by teachers in responding to challenges in 21st-century learning. The writing in this study uses a literature study by utilizing scientific journals published by the Creative Mathematics Journal- Innovative (KREANO) from 2016 to 2021 by involving a total of 156 scientific journal items. The theme of last year's study was dominated by the process of mathematical thinking skills with a focus on secondary education students as research subjects. Currently, the research theme of mathematics education is studying with a focus on developing media or making a product and learning device as well as designing a project-based learning model with a subject focus on prospective teachers and students of secondary education as research subjects. Future research in mathematics education will also examine mathematical thinking skills by creating technology-assisted learning in an open, flexible project-based learning environment so that students can collaborate in developing their potential. Therefore, teachers are required to be able to implement a curriculum to innovate in learning with various approaches, models, strategies, methods, assessments, and all related matters, which are effective